Long-term economic consequences of Vietnam-era conscription: schooling, experience and earnings - Joshua D. Angrist; Stacey H. Chen (Institute for the Study of Labor (IZA), 2008)
Military service reduces civilian labor market experience but subsidizes higher education through the GI Bill. Both of these channels are likely to affect civilian earnings. New estimates of the effects of military service using Vietnam-era draft-lottery instruments show post-service earnings effects close to zero in 2000, in contrast with earlier results showing substantial earnings losses for white Vietnam veterans in the 1970s and 1980s. The recent estimates also point to a marked increase in post-secondary schooling that appears to be attributable to the Vietnam-era GI Bill. Seen through the lens of a Mincer wage equation, the wage effects observed in 2000 data can be explained by a flattening of the experience profile in middle age and a modest return to the additional schooling funded by the GI Bill. In particular, IV estimates of the returns to GI Bill-funded schooling are well below OLS estimates. Wage equations that allow for nonlinearities in the returns to schooling and a possible negative effect of military service on health, leave the main findings unchanged.
urn:nbn:de:101:1-20080820139
Keywords: J31; 330; Veterans; returns to schooling; instrumental variables; Wehrdienst; Krieg; Soziale Folgen; Bildungsverhalten; Bildungsniveau; Einkommen; Gesundheit; USA; Vietnam